DIAGENESIS AND THE RECONSTRUCTION OF PALEOENVIRONMENTS: A METHOD TO RESTORE ORIGINAL ?18O VALUES OF CARBONATE AND PHOSPHATE FROM FOSSIL TOOTH ENAMEL - Zazzo A.; Lecuyer C.; Sheppard S.M.F.; Grandjean P.; Mariotti A. (My University, 2004)
Intra-tooth δ18O variations within the carbonate (δ18Oc) and phosphate (δ18Op) components of tooth apatite were measured for Miocene and Pliocene hypsodont mammals from Afghanistan, Greece and Chad in order to evaluate the resistance of enamel to diagenetic alteration. Application of water-apatite interaction models suggest that the different kinetic behaviours of the phosphate-water and carbonate-water systems can be used to detect subtle oxygen isotope disequilibria in fossil enamel when intra-individual variations are considered. Selective alteration of the oxygen isotope composition from the carbonate component of Afghan and Greek enamels suggests inorganic isotopic exchange processes. Microbially-induced isotopic exchange for phosphate is demonstrated for the first time in enamel samples from Chad, in association with extensive recrystallization. In Chad, δ18Op values were derived from partial isotopic exchange with fossil groundwater during early diagenesis. Mass balance calculations using average carbonate content in enamel as a proxy for recrystallization, and the lowest δ18Op value of dentine as a proxy for the isotopic composition of the diagenetic fluid, indicate that diagenesis can alter δ18Op by as much as 3‰ in some enamel samples. This diagenetic alteration is also responsible for a decrease in intra-individual variations of up to 1‰ in affected specimens. The effects of diagenesis on δ18Op values of fossil enamel are not systematic, however, and can only be estimated if sequential δ18Op and δ18Oc analyses are performed on fossil enamel and dentine. Reconstruction of large temporal- or spatial-scale paleoclimates based on δ18Op analyses from mammalian teeth cannot be considered valid if enamel has been affected by bacterial activity or if the data cannot be corrected for diagenetic effects.